B-doped diamond field-effect transistor with ferroelectric vinylidene fluoride–trifluoroethylene gate insulator. (15th September 2017) - Karaya, Ryota; Baba, Ikki; Mori, Yosuke; Matsumoto, Tsubasa; Nakajima, Takashi; Tokuda, Norio; Kawae, Takeshi
Abstract: A B-doped diamond field-effect transistor (FET) with a ferroelectric vinylidene fluoride–trifluoroethylene (VDF–TrFE) copolymer gate insulator was fabricated. The VDF–TrFE film deposited on the B-doped diamond showed good insulating and ferroelectric properties. Also, a Pt/VDF–TrFE/B-doped diamond layered structure showed ideal behavior as a metal–ferroelectric–semiconductor (MFS) capacitor, and the memory window width was 11 V, when the gate voltage was swept from 20 to −20 V. The fabricated MFS-type FET structure showed the typical properties of a depletion-type p-channel FET and a maximum drain current density of 0.87 mA/mm at room temperature. The drain current versus gate voltage curves of the proposed FET showed a clockwise hysteresis loop owing to the ferroelectricity of the VDF–TrFE gate insulator. In addition, we demonstrated the logic inverter with the MFS-type diamond FET coupled with a load resistor, and obtained the inversion behavior of the input signal and a maximum gain of 18.4 for the present circuit.